REFORMASI BIROKRASI MELALUI PROSES PELAYANAN IZIN MENDIRIKAN BANGUNAN DI KABUPATEN ROKAN HILIR PROVINSI RIAU - Abdurohim, Abdurohim (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
The reform of the bureaucracy in both the Central Government and local authorities is a necessity in efforts to bring about good governance. Improvements in implementing the Government-oriented community service functions, should be placed on public organizations. As a public organization is an organization that most often get in touch directly with the community to provide services. Therefore, improvements in the conduct of public organizations to do, especially how to cultivate and improve the performance of the apparatus in the service as a State and a society which inevitably must strive to enhance the ability of the works to the maximum extent possible. Since the implementation of the tasks of the Ministry of the Republic by the organization is very dependent on the competence of its officials. Whereas the community can only assess the quality of service received in any affair that she did. The Ministry is providing help or relief to others both material and non material so that others can solve the problem on its own. Assessment of a quality service according to the terms of reability Parasuraman, responsiveness, assurance, emphaty and tangibles. This research was carried out in the service of Copyright works and Rokan Hilir Spatial Districts, where the informer is a research service provider, service desk and observers about the IMB. Data collection was carried out with the technical interview and observation, after the data collected was then analysed using descriptive analysis with qualitative techniques. From the results obtained that the IMB services is assessed reability, responsiveness, assurance, amphaty and the tangibles of The Copyrighted work and The Spaces have not been going well. While the factors that inhibit the Copyright Agency of the Ministry of Works in IMB and Rokan Hilir Regency Floorplan is the ability of employees, facilities and availability of personnel.